Optimization and evaluation of reconstruction-based compensation methods and reconstruction parameters for Tc-99m MIBI parathyroid SPECT. Issue 2 (March 2015) - Ekjeen, Tawatchai; Tocharoenchai, Chiraporn; Pusuwan, Pawana; Fung, George S.K.; Ghaly, Michael; Du, Yong; Frey, Eric C.
Abstract: The value of Tc-99m MIBI parathyroid SPECT for localizing parathyroid hyperplasia in chronic renal failure patients remains inconclusive due to limited image quality. Advanced reconstruction methods to improve image quality have been developed but require optimization and evaluation. The goal of this study was to optimize and evaluate compensation methods and reconstruction parameters for Tc-99m MIBI parathyroid SPECT. A phantom population and projection data that modelled clinically realistic variations found in patients were simulated. The 3D OS-EM reconstruction with compensation for attenuation, detector response and scatter in various combinations were studied. For each compensation, the number of updates for OS-EM and the cutoff frequency of a 3D Butterworth filter were optimized and evaluated using anthropomorphic model observer. With optimal parameters, the method with compensation for attenuation and detector response, with or without the addition of scatter compensation, provided the highest lesion detectability for Tc-99m MIBI parathyroid SPECT. Highlights: Higher cutoff frequencies are optimal to preserve information about the defect. Small iteration numbers are required to keep the relatively modest noise levels. The method incorporating all compensations provided the highest improvement of image quality. Detector response compensation would be a benefit for detection of resolution-limited objects. The benefit of scatter compensation are relatively small for Tc-99m MIBI parathyroid SPECT.